WOMEN IN THE QUR’AN: SURAH AL-BAQARAH/2: 233 - U. Saifuddin ASM; Ulvah Nur'aeni (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This study examines verse 233 of Surah Al-Baqarah from the Quran, which addresses the responsibilities of mothers in breastfeeding their children and the duties of fathers in providing for the nursing mothers. The verse emphasizes that mothers should breastfeed their children for two complete years if they wish to complete the nursing period. It also states that the father is responsible for providing food and clothing to the nursing mothers in a reasonable manner, according to it means. The verse further clarifies that no one should be burdened beyond their capacity and that neither the mother nor the father should be made to suffer because of their child. If both parents desire weaning by mutual consent and consultation, there is no blame upon them. Additionally, if parents wish to have their children nursed by a substitute, there is no blame upon them as long as they pay what is acceptable in a reasonable manner. The verse concludes by advising to be conscious of Allah and know that Allah is all-seeing of what you do. This study analyzes the verse from various perspectives, including its historical context, linguistic analysis, general interpretation, and application in different disciplines such as education, women's rights, and postmodernism. The findings highlight the Quran's emphasis on the rights and responsibilities of both parents, the importance of breastfeeding, and the need for mutual consultation and reasonable conduct in family matters.